Portable Smart Door base on Arduino and Artifical Neural Network for Temperature and Face Mask Detection - Fitrya, Neneng; Ginting, Delovita; Wirman, Shabri Putra; Anggreani, Selvia; Ariyani; Syahputra, Romi Fadli (JST (Jurnal Sains dan Teknologi), 2023)
Temperature checks and wearing masks are an effort to reduce the transmission of Covid-19. Manual checking is impractical and spent time screening many people in public areas. This work propose a portable smart door that simultaneously detects the body temperature and mask of the people. Temperature detection uses MLX90614 sensor and Arduino, while mask recognition uses digital camera with artificial neural network (ANN). Component test and completion test are conducted to examine the smart door performance involving 20 volunteers. The door was tested to measure the body temperature of the volunteers with and without a mask. The measured temperature was compared with measurements of a thermal gun. The door will open automatically if the temperature is below 37.2°C and wearing a mask, while remaining closed if above 37.2°C or not wearing a mask. The temperature sensor works properly with a small deviation and saving time almost half of thermalgun response time. The accuracy of mask detection by the ANN is also at a high level of confidence. These findings demonstrate the applicability of the smart door for screening body temperature and mask in public areas for faster and precise.